The impact of surgical timing on outcome in acute appendicitis in adults: a retrospective observational population-based cohort study - Uttinger, Konstantin L.; Baum, Philip; Diers, Johannes; Seehofer, Daniel; Germer, Christoph-Thomas; Wiegering, Armin (International journal of surgery, 2024)
Background: - Acute appendicitis is a global disease with high incidence. The main objective was to assess the association between time from admission to surgery (TAS) and surgery during emergency hours with operative outcome in light of conflicting evidence. - Methods: - This is a retrospective population-wide analysis of hospital billing data (2010-2021) of all adult patient records of surgically treated cases of acute appendicitis in Germany by TAS. The primary outcome was a composite clinical endpoint (CCE; prolonged length of stay, surgical site infection, interventional draining after surgery, revision surgery, ICU admission and/or in-hospital mortality). Cases of complicated appendicitis were identified using diagnosis (ICD-10) and procedural codes (resection beyond appendectomy). - Results: - 855 694 patient records were included, of which 27·6% (236,481) were complicated cases of acute appendicitis. 49·0% (418,821) were females and median age was 37 (interquartile range 22·5-51·5). Age, male sex, and comorbidity were associated with an increased proportion of CCE and in-hospital mortality. TAS was associated with a clinically relevant increase of CCE after 12 h in complicated appendicitis [Odd’s ratio (OR), 1·19, 95% CI: 1·14-1·21] and after 24 h in uncomplicated appendicitis (OR 1·10, 95% CI: 1·02-1·19). Beyond the primary endpoint, the proportion of complicated appendicitis increased after TAS of 72 h. Surgery during emergency hours (6 pm-6.59 am) was associated with an increase of CCE and mortality (OR between 1·14 and 1·49). Age, female sex, night-time admission, weekend admission, a known previous surgery, obesity, and therapeutic anticoagulation were associated with delayed performance of surgery. - Conclusion: - This work found an increase of a CCE after TAS of 12 h for complicated appendicitis and an increase of the CCE after TAS of 24 h for uncomplicated appendicitis with a stable proportion of complicated appendicitis in these time windows. Both CCE and mortality were increased if appendectomy was performed during emergency hours.